L’impossible « chambre des horreurs » du Museum of Ornamental Art : une archéologie du design criminel - Marchand, Marie-Ève (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2014)
In 1852, the Museum of Ornamental Art, today the Victoria and Albert Museum, opened its doors to the public. Taking part in a general reform of the British art and design education system, the museum sought to instill what were considered good design principles. To do so, a museographic strategy that proved to be as popular as it was controversial was chosen: the exhibition gallery entitled “Decorations on False Principles,” which immediately became known as the “Chamber of Horrors.” This gallery, a dogmatic expression of the functionalist conception of ornament advocated by the museum, referred through its nickname to another then famous Chamber of Horrors, the one in Mme Tussaud’s wax museum. In this paper, I will first argue that the Museum of Ornamental Art’s Chamber of Horrors is an early example of the association of ornament with crime that reappears in later design theories. Second, by examining the means taken to transmit the idea of the criminalization of ornaments designed after “bad principles,” I demonstrate why the concept of the Chamber of Horrors is in itself doomed to failure. I thus analyze this uncommon exhibition as a manifestation of the museum’s aesthetic philosophy and mechanisms at a time when the institution’s modalities were still in the process of elaboration.